Penentuan Tingkat Erosi dan Perencanaan Konservasi Lahan di Sub DAS Telagawaja Kabupaten Karangasem Provinsi Bali - Made Sri Sumarniasih; Ni Made Trigunasih; Michael Surbakti (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2023)
The increasing use of natural resources due to population growth and economic development, as well as low public awareness of natural resource conservation, has an impact on accelerating damage to river watersheds. The research aims to determine the level of erosion and its distribution, permitted erosion, conservation planning in the Telagawaja Sub-watershed. The research uses a survey method in taking soil samples based on homogeneous land unit maps. Soil samples were analyzed in the laboratory, erosion calculations used the USLE method. The research results show that the Telagawaja sub-watershed has erosion levels ranging from very light to heavy (0.99-472.19 tons/ha/year). Very light erosion 0.99; 1.53; 5.36 tons/ha/year is found in Homogeneus Land Unit (HLU) I, II, and VII. Heavy erosion 186.64; 221.43; 367.14; 472.19 tons/ha/year is found in HLU V, VI, IV, III. Permissible erosion in the Telagawaja sub-watershed is 11-36.1 tons/ha/year, spread across HLU I is 12.82 tons/ha/year; HLU II of 36.10 tons/ha/year; HLU III of 21.73 tons/ha/year; HLU IV of 24.48 tons/ha/year; HLU V of 13.55 tons/ha/year; HLU VI of 11.00 tons/ha/year; HLU VII is 15.05 tons/ha/year. Conservation actions that can be carried out are by increasing the plant management factor (C) of peanuts with straw mulch of 4 tons/ha (HLU III, IV, V and VI), increasing land management actions by making terracing with medium construction benches (HLU III and IV) and good bench terrace construction (HLU V and VI).